2017
DOI: 10.1111/mmi.13709
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a peptidoglycan‐like structure in Orientia tsutsugamushi

Abstract: Summary Bacterial cell walls are composed of the large cross-linked macromolecule peptidoglycan, which maintains cell shape and is responsible for resisting osmotic stresses. This is a highly conserved structure and the target of numerous antibiotics. Obligate intracellular bacteria are an unusual group of organisms that have evolved to replicate exclusively within the cytoplasm or vacuole of a eukaryotic cell. They tend to have reduced amounts of peptidoglycan, likely due to the fact that their growth and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 67 publications
4
28
0
Order By: Relevance
“…Highly elongated cells of R. typhi growing in a tick cell line have been reported 53 suggesting the possibility that mechanisms for producing different cell morphologies under different conditions may be widespread across the Rickettsiaceae, The morphology of growing Ot, and possibly other rickettsia, may reflect nutrient availability under different conditions. The observation that elongated Ot cells are rod shaped rather than spherical supports the recent finding that Ot synthesizes a peptidoglycan-like structure, although this is not very abundant 43 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Highly elongated cells of R. typhi growing in a tick cell line have been reported 53 suggesting the possibility that mechanisms for producing different cell morphologies under different conditions may be widespread across the Rickettsiaceae, The morphology of growing Ot, and possibly other rickettsia, may reflect nutrient availability under different conditions. The observation that elongated Ot cells are rod shaped rather than spherical supports the recent finding that Ot synthesizes a peptidoglycan-like structure, although this is not very abundant 43 .…”
Section: Discussionsupporting
confidence: 81%
“…The observation that bacteria mostly initiate protein synthesis upon exposure to the cytoplasm raised the question: what triggers the resumption of metabolic activity in intracellular Ot? We have previously shown that the bacterial outer membrane protein TSA56 forms a disulfide crosslinked network 43 . We hypothesized that this, and potentially other proteins containing exposed Cys residues, might become reduced upon exposure to the reducing environment of the host cell cytoplasm and that this might trigger an internal signal to activate metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has provided evidence that O. tsutsugamushi may possess a minimal peptidoglycan-like structure and is sensitive to a range of non-ß-lactam peptidoglycan-targeting antibiotics such as D-cycloserine and phosphomycin, but remains insensitive to all ß-lactams tested, which might be explained by an intrinsic insensitivity by the class B PBPs of this organism (Atwal et al, 2017) or an unknown beta-lactamase. O. tsutsugamushi was also shown to possess a disulphide cross-linked protein network on the outer membrane, analogous to the Chlamydiae (Atwal et al, 2017). The Anaplasmataceae comprise a group of tickborne human and veterinary pathogens.…”
Section: Rickettsialesmentioning
confidence: 99%
“…O. tsutsugamushi lacks the enzyme catalysing the final step of meso-DAP biosynthesis, DapF. Whilst no direct alternative to this enzyme has been described, a recent study showed the presence of meso-DAP in purified O. tsutsugamushi by mass spectrometry, suggesting the presence of an unidentified alternative gene or pathway (Atwal et al, 2017). Surprisingly, E. ruminantium possesses a complete set of genes required for meso-DAP biosynthesis, although it lacks MurE that would be required to incorporate it into the peptidoglycan precursor.…”
Section: Biosynthesis Of Peptidoglycan Precursorsmentioning
confidence: 99%